2014
DOI: 10.1007/s40615-014-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Cardiovascular Care: A Review of Culprits and Potential Solutions

Abstract: Cardiovascular disease is the leading cause of death for white and black Americans. Despite the presence of therapies that improve survival and quality of life in cardiac patients, African-Americans continue to have the worst heart disease survival rates of all racial groups. The literature has described racial disparities in cardiovascular care for at least 25 years. We review the current status of racial disparities in four areas of cardiovascular care: automatic implantable cardioverterdefibrillator (AICD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…Patients' race influencing the physician's referral for cardiac procedures has also been reported as one of the influential factors. Sedlis and colleagues reported the higher odds (OR =1.70) of referral for surgery for Caucasian than African Americans (24,26,27). Lower household income among blacks and the type of hospital facility have been found to play key roles in the nature of the care being provided (9).…”
Section: Discussionmentioning
confidence: 99%
“…Patients' race influencing the physician's referral for cardiac procedures has also been reported as one of the influential factors. Sedlis and colleagues reported the higher odds (OR =1.70) of referral for surgery for Caucasian than African Americans (24,26,27). Lower household income among blacks and the type of hospital facility have been found to play key roles in the nature of the care being provided (9).…”
Section: Discussionmentioning
confidence: 99%
“…Our facility provides care to a higher percentage of black patients than other comparably sized centers providing specialized cardiovascular surgical services. Historically, this group has experienced differences in access to care and discrimination [44,45]. Our results also are not applicable to an increasingly younger (intermediate risk) population of patients undergoing TAVR [46].…”
Section: Discussionmentioning
confidence: 88%
“…Racial and ethnic inequities have been documented in nearly all areas of medicine, 21 and in particular in cardiology 13 , 14 , 15 and the surgical management of AS. 12 , 16 , 17 , 18 , 19 , 27 , 28 In a single‐center study of 880 patients with severe AS by echocardiography from 2004 to 2010, Yeung and colleagues found that Black patients were less likely to undergo AVR (39% versus 53%, P =0.02) and more likely to refuse AVR (33% versus 20%, P =0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic inequities in medical care are well documented in SAVR as well as in cardiology and medicine more generally, particularly with new technologies. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Early indications are that TAVR is no different; the trial of a balloon‐expandable prosthesis in low‐risk patients was the only pivotal TAVR trial to report the proportion of non‐White patients included (8.7%). 9 Black, Hispanic, and other racial and ethnic groups comprised only 3.8%, 3.4%, and 1.5%, respectively, of patients undergoing TAVR with a Food and Drug Administration‐approved device from November 2011 to June 2016, numbers markedly disproportionate to the racial and ethnic composition of the US population.…”
mentioning
confidence: 99%